Clinical application of near infrared fiber optic spectroscopy for noninvasive bone assessment. Issue 4 (5th February 2020) - Shanas, No'ad; Querido, William; Dumont, Alexander; Yonko, Elizabeth; Carter, Erin; Ok, Jina; Karchner, James P.; Barbe, Mary F.; Ali, Sayed; Patil, Chetan; Raggio, Cathleen; Pleshko, Nancy
Abstract: Approaches for noninvasive bone quality assessment are of great clinical need, particularly in individuals that require close monitoring of disease progression. X‐ray measurements are standard approaches to assess bone quality; however, they have several disadvantages. Here, a nonionizing approach for noninvasive assessment of the second metacarpal bone based on near infrared (NIR) spectroscopy was investigated. Transcutaneous bone signal detection was experimentally confirmed with cadaveric hand data, and Monte Carlo modeling further indicated that 50% of the measured signals arise from bone. Spectral data were collected via a NIR fiber optic from the bone of individuals with osteogenesis imperfecta, a disease marked by frequent bone fractures and fragility. Multiple significant correlations were found between spectral parameters related to water, protein and fat, and standard bone quality parameters obtained by X‐ray measurements. The results from this preliminary study highlight the potential application of NIR spectroscopy for the noninvasive assessment of bone quality. Abstract : Near infrared (NIR) spectroscopy is used for noninvasive assessment of bone quality in a population of subjects with the bone disease osteogenesis imperfecta. NIR spectral data were obtained transcutaneously from the second metacarpal via fiber optic probe. Several spectral parameters correlated with bone quality parameters, which highlights an innovative first step in the development of a nonionizing modality that could enhance clinical diagnosis and disease management.